THE STRATEGY OF INFORMAL SECTOR TRADERS TO FACE PANDEMIC COVID-19 IN MAROS CITY - Iriani, Iriani; Bahri, Syamsul (Kementerian Pendidikan dan Kebudayaan, 2021)
The informal sector is a sector that has a huge impact during pandemic covid-19, because they cannot do their usual activities. The governmentâ€™s policy in the form of PSBB restricts their movements to run their business, such as meatball and vegetable seller and who are in the front of the shops. This research described the strategy used by meatball and vegetable sellers during pandemic. The research method used was descriptive qualitative. Data were collected through interview, observation, and library study. The study result showed that during pandemic covid-19, the informal sector traders felt the decrease sales impact of which affected the income of meatball and vegetable traders, thus reducing their trading capital. They were in dilemma for wanting to run business and afraid of being to covid-19. Therefore, the meatball seller dealt by making various efforts so that their family needs are met and their business still survived by changing the marketing system selectively for goods being marketed and changing the debt-payment mechanism.Â